Findings in exudates can help distinguish benign gastric ulcers from ulcerated adenocarcinomas. Issue 2 (3rd May 2018) - Hissong, Erika; Jessurun, Jose; Yantiss, Rhonda K
Abstract : Aims: Most gastric carcinomas develop in association with mucosal atrophy and hypochlorhydria, whereas benign peptic ulcers are acid‐related. Given that acid sterilises the gastric contents, we hypothesised that ulcerated gastric cancers may be associated with increased numbers of luminal microorganisms as compared with peptic ulcers, and that this feature may represent a helpful diagnostic clue to the presence of malignancy. We performed this study to determine whether the features of luminal debris, including microorganisms, from ulcerated gastric cancers were significantly different from those of debris associated with benign ulcers. Methods and results: We retrospectively identified 50 ulcerated adenocarcinomas and 50 site‐matched peptic ulcers. Luminal debris was evaluated for the nature of inflammation, necrosis, and the presence of mixed bacterial colonies or yeasts. Non‐lesional mucosa was assessed for chronic gastritis, Helicobacter pylori, chemical gastropathy, and intestinal metaplasia. Patients in both groups were adults (mean age: 69 years and 62 years, respectively) with similar amounts of inflammation and cellular necrosis in biopsy material. However, 76% of ulcerated cancers harboured non‐ H. pylori bacterial colonies, as compared with only 22% of peptic ulcers ( P < 0.01). Filamentous bacteria and fungi were highly specific for carcinoma (98% and P = 0.02 for both comparisons). Background intestinal metaplasia was more common among gastric cancers than among peptic ulcers (50% versus 26%, P = 0.02), whereas chemical gastropathy was more commonly associated with the latter (50% versus 10%, P < 0.01). Conclusion: Gastric cancers may be colonised by non‐ H. pylori microorganisms. Detection of numerous bacterial colonies, filamentous bacteria or fungi in biopsy material obtained from ulcerated gastric lesions should raise suspicion for underlying malignancy.